EFFECTS OF RESPONDING TO A NAME AND GROUP CALL ON PRESCHOOLERS' COMPLIANCE - Beaulieu, Lauren (The Society for the Experimental Analysis of Behavior, 2012)
We assessed teacher–child relations with respect to children's name calls, instructions, and compliance in a preschool classroom. The most frequent consequence to a child's name being called was the provision of instructions. We also observed a higher probability of compliance when children attended to a name call. Next, we evaluated the effects of teaching preschoolers to attend to their names and a group call on their compliance with typical instructions. We used a multiple baseline design across subjects and a control-group design to evaluate whether gains in compliance were a function of treatment or routine experience in preschool. Results showed that compliance increased as a function of teaching precursors for all children in the experimental group, and the effects on compliance were maintained despite a reduction of the occurrence of precursors. Moreover, it appeared that precursor teaching, not routine preschool experience, was responsible for the changes in compliance.